Phytochemical content of Maluku nutmeg (Myristica fragrans Houtt) in Inhibiting Skin Pathogenic Bacteria - Wally, Pramita; Marwah, Andi Sitti (Journal of Tropical Crop Science, 2023)
Banda nutmeg (Myristica fragrans Houtt) is one of the native species of Maluku that has various benefits other than as a cooking spice. Nutmeg, especially its fruit, offers significant advantages in the medical field as a natural dermatological product, effectively treating skin infections caused by pathogens. One such bacterial infection is pyoderma, characterized by the presence of pus-producing bacteria, leading to the formation of pustules or greenish-yellow crusts upon examination. Among the bacteria responsible for skin infections, Pseudomonas aeruginosa and Methicillin Resistant Staphylococcus aureus (MRSA) are notable bacterial species that cause skin infections. The active compounds found in nutmeg act as antibacterial agents by interfering with the peptidoglycan components within bacterial cells. This interference results in the formation of intact cell walls, ultimately leading to bacterial cell death. This study aimed to identify the bioactive profile of Maluku nutmeg extract metabolites and assess their inhibitory effects on pathogenic bacteria, specifically P. aeruginosa and MRSA, responsible for skin infections. The study revealed the presence of various bioactive compounds in nutmeg extract, including alkaloids, flavonoids, terpenoids, phenols, and tannins. Notably, the application of nutmeg pulp at an 80% concentration proved highly effective in inhibiting bacterial growth, surpassing the efficacy of the positive control. The enhanced effectiveness against MRSA, compared to P. aeruginosa, can be attributed to the higher concentration of secondary metabolites present in nutmeg extracts.